Biological and pharmacological evaluation of dimethoxycurcumin: A metabolically stable curcumin analogue with a promising therapeutic potential. Issue 1 (31st March 2017) - Teymouri, Manouchehr; Barati, Nastaran; Pirro, Matteo; Sahebkar, Amirhosein
Abstract : Dimethoxycurcumin (DiMC) is a synthetic analog of curcumin with superior inter‐related pro‐oxidant and anti‐cancer activity, and metabolic stability. Numerous studies have shown that DiMC reserves the biologically beneficial features, including anti‐inflammatory, anti‐carcinogenic, and cytoprotective properties, almost to the same extent as curcumin exhibits. DiMC lacks the phenolic‐OH groups as opposed to curcumin, dimethoxycurcumin, and bis‐demethoxycurcumin that all vary in the number of methoxy groups per molecule, and has drawn the attentions of researchers who attempted to discover the structure‐activity relationship (SAR) of curcumin. In this regard, tetrahydrocurcumin (THC), the reduced and biologically inert metabolite of curcumin, denotes the significance of the conjugated α, β diketone moiety for the curcumin activity. DiMC exerts unique molecular activities compared to curcumin, including induction of androgen receptor (AR) degradation and suppression of the transcription factor activator protein‐1 (AP‐1). The enhanced AR degradation on DiMC treatment suggests it as a novel anticancer agent against resistant tumors with androgenic etiology. Further, DiMC might be a potential treatment for acne vulgaris. DiMC induces epigenetic alteration more effectively than curcumin, although both showed no direct DNA hypomethylating activity. Given the metabolic stability, nanoparticulation of DiMC is more promising for in vivo effectiveness. However, studies in this regard are still in its infancy. In the current review, we portray the various molecular and biological functions of DiMC reported so far. Whenever possible, the efficiency is compared with curcumin and the reasons for DiMC being more metabolically stable are elaborated. We also provide future perspective investigations with respect to varying DiMC‐nanoparticles. Abstract : This review, being the first of its kind, is a comprehensive evaluation of the molecular, cellular, and clinical properties of dimethoxycurcumin as a promising analog of curcumin. We have discussed various molecular and biological functions of DiMC reported so far. Whenever possible, the efficiency compared with curcumin and the reasons for DiMC being more metabolically stable than curcumin has been explained. We have also provided future perspective investigations with respect to varying DiMC‐nanoparticles.